BIM-Based Optimization of Drilling Angle and Hole Position of Outside Corner Anchor Rods - Zihan Jiao; Xuefeng Zhao; Danyang Li; Zhe Sun; Wangbing Li (Applied Sciences, 2023)
In recent years, safety issues involving foundation pits have attracted extensive attention in the industry. The external angle of the foundation pit bears a greater load and is more prone to collapsing. Anchor support technology is one of the most widely used support technologies in construction engineering, but it has the problem of anchor rod crossing and colliding from the initial design stage, and this reduces anchoring force and eventually leads to many safety issues. Compared with traditional methods, Building Information Modeling (BIM) technology can save a lot of time as well as reduce costs, and applying it to concealed engineering can solve the problems that exist during the design stage and reduce unpredictable construction risks. This study proposes an optimization method based on BIM that can accurately and quickly optimize the drilling of anchor rods in the external angles of foundation pits. The results show that the proposed method can reduce the number of anchor rod collision points at the external angle of the foundation pit, minimize the loss of horizontal force caused by anchor rod collision, and ensure the safety and stability of the foundation pit support system.